Numerical modelling of rock fractures filled with chemical grout - Toh, Hong Liang (Nanyang Technological University, 2023)
Chemical grouting is a popular technique used in geotechnical engineering to improve quality of rock masses. This project aims to analyze how the usage of chemical grout with and without sand can improve the rock mass quality using numerical modelling. Through numerical simulation, the project focuses on reproducing and visualizing flow rate distribution on rock-grout interface and how grouting contributes to fracture permeability reduction.